Selenium-chitosan alleviates the toxic effects of Zearalenone on antioxidant and immune function in mice - Qin, Shunyi; She, Fuze; Zhao, Fanghong; Li, Liuan; Chen, Fu (Frontiers in Veterinary Science, 2022)
This study assessed the protective effects of selenium-chitosan (SC) against antioxidant and immune function-related damage induced by zearalenone (ZEN) in mice. In total, 150 female mice were allotted to five groups for a 30-day study. Control mice were fed a basal diet. Mice in the ZEN, ZEN-Se1, ZEN-Se2 and ZEN-Se3 groups were fed the basal diet supplemented with same dose of ZEN (2 mg/kg) and different doses of SC, 0.0, 0.2, 0.4 and 0.6 mg/kg, respectively (calculated by selenium). After 30 days, the total antioxidant capacity (T-AOC) level, glutathione peroxidase (GSH-Px) activity, total superoxide dismutase (T-SOD) activity and malondialdehyde (MDA) content in plasma and liver, as well as Con A-induced splenocyte proliferation, plasma interleukins concentrations and liver interleukin mRNA expression levels were determined. The plasma and liver GSH-Px activities, liver T-AOC levels, Con A-induced splenocyte proliferation, interleukin (IL) contents and mRNA expression levels in the ZEN group were significantly lower than in the control group (P < 0.01 or P < 0.05), whereas plasma and liver MDA contents in the ZEN group were significantly higher than in the control group (P < 0.01 or P < 0.05). Additionally, plasma and liver GSH-Px activities, liver T-AOC levels, Con A-induced splenocyte proliferation, IL-1β, IL-17A, IL-2 and IL-6 contents and mRNA expression levels in ZEN+Se2 and ZEN+Se3 groups were significantly higher than in the ZEN group (P < 0.01 or P < 0.05), whereas plasma and liver MDA contents in the ZEN+Se2 and ZEN+Se3 groups were significantly lower than in the ZEN group (P < 0.01 or P < 0.05). The plasma and liver GSH-Px activities, Con A-induced splenocyte proliferation, IL-1β and IL-6 contents, IL-2 and IL-17A mRNA expression levels in the ZEN+Se1 group were also significantly higher than in the ZEN group (P < 0.01 or P < 0.05), whereas the plasma MDA content in the ZEN+Se1 group was also significantly lower than in the ZEN group (P < 0.01). Thus, SC may alleviate antioxidant function-related damage and immunosuppression induced by ZEN in mice.